KETERKAITAN ANTARA BUDAYA HIDUP DENGAN SETTING PERILAKU MASYARAKAT DI JALAN DI.PANJAITAN YOGYAKARTA - Sanitha, Onie Dian; Rosalia, Alderina; Purwani S., Ni Made Bulan; Putu E., I. Gusti Ngurah; Margaretha, Maria (JURNAL PERSPEKTIF ARSITEKTUR, 2023)
The Philosophical Axis Corridor on Jalan DI. The Panjaitan towards the Krapyak Stage, Yogyakarta, has a historical value which implies a Philosophical Image as a noble cultural heritage as an influential path in forming the City Image. This road corridor which is about 3 kilometers long has special characteristics seen from the appearance of the buildings along the various and rhythmic road corridors, as if they have a specific purpose that represents the meaning of the path traversed by this philosophical axis. The appearance of this building also influences the daily culture of the surrounding community so that the appearance of the building reflects the contents of the building itself. As a reference for observation, some relevant data is used to support the observation process to find answers to unique phenomena along the Panggung Krapyak axis corridor. The difference in each building that seems to be rhythmic in the Jl.DI Panjaitan Corridor when viewed from an anthropological perspective, has a diverse background which is highlighted from the point of view of the social values of a developing community to produce a cultural form with character so that it has an impact on the appearance of the building and its diverse scope and rhythmic. It is found that the size and area of the building are gradually getting bigger towards the north, as if this change represents a special meaning from the philosophical axis, namely the journey of a small child to maturity.